Formulation and Evaluation of an Antifungal Ointment Containing Zingiber officinale Roscoe (Zingiberaceae) Essential Oil as Active Principle - Nelly Tagnin Nkuete; Sandra Leila Nnanga; Stephanie Tamdem Guetchueng; Nga Nnanga; Joseph Ngoupayo (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2022)
The increase incidence of fungal infections, the resistance of fungal strains to existing drugs and the toxicity assimilated to long term usage of antifungal drugs as prompted the search of new alternative from natural source. In this study we have evaluated the antifungal properties of the essential oil of the rhizome of Z. officinale, a plant known for its various biological properties and used in food industry as spice. An antifungal ointment with Z. officinale essential oil as active principle was also formulated and its antifungal properties evaluated. GC/MS analysis identified Zingiberene (22.36%), 1.8-cineole (15.54%), geranial (11.91%), camphene (11.09%) and geraniol (8.75%) as the main constituents of Z. officinale essential oil obtained by hydrodistillation. The oil showed a significant antifungal activity against clinical isolate of Candida krusei with MIC 800 ppm by microdilution method. The formulated ointment containing 10 % glycerol, 60 % vaseline, 8 % hydrosol, 20% lanolin and 2% Zingiber officinale essential oil (Formule E1) was found to follow pharmaceutical standards according to European Pharmacopeia and also showed good antifungal properties